2022
DOI: 10.3389/fimmu.2022.883404
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Preeclampsia: Genetic Biomarkers, Mechanisms, and Therapeutic Strategies

Abstract: ObjectivePreeclampsia is a common and serious complication of pregnancy, posing a threat to maternal and fetal safety due to the lack of effective biomarkers and treatment strategies. This study aimed to identify potential biomarkers that can be used to predict preeclampsia and identify the molecular mechanisms of preeclampsia pathogenesis and drug prediction at the transcriptome level.MethodsWe analyzed differential expression genes (DEGs) in preeclampsia and non-preeclampsia groups in the GSE75010 dataset, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Consistent with our results, a cohort study [24] exploring the effect of AVP gene variation and plasma copeptin on the risk of diabetes did not find a significant association between the polymorphisms of rs3761249 and rs2282018 and copeptin concentration in women but found an association between the polymorphisms of two loci and copeptin in men. The genetic contributions to preeclampsia are likely to be complex, in addition, to directly causing preeclampsia by encoding proteins, the genes involved may alter the expression of RNA or lower a woman's biological threshold at which she would develop the condition [25,26]. However, the current study has not detected the expression of RNA, so it is unavailable to analyze whether the variation of the AVP gene affects the occurrence of GH and PE through the expression amount of the gene.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with our results, a cohort study [24] exploring the effect of AVP gene variation and plasma copeptin on the risk of diabetes did not find a significant association between the polymorphisms of rs3761249 and rs2282018 and copeptin concentration in women but found an association between the polymorphisms of two loci and copeptin in men. The genetic contributions to preeclampsia are likely to be complex, in addition, to directly causing preeclampsia by encoding proteins, the genes involved may alter the expression of RNA or lower a woman's biological threshold at which she would develop the condition [25,26]. However, the current study has not detected the expression of RNA, so it is unavailable to analyze whether the variation of the AVP gene affects the occurrence of GH and PE through the expression amount of the gene.…”
Section: Discussionmentioning
confidence: 87%
“…A case-control study from Turkey [17] reported that plasma levels of copeptin in the third trimester of pregnancy were 0.31AE0.09ng/ml, 0.62 AE 0.16 ng/ml, and 0.85 AE 0.18 ng/ml among women with normal blood pressure, mild preeclampsia and severe preeclampsia (P < 0.001), respectively. Yeung et al [14] measured serum copeptin three times using samples collected longitudinally during pregnancy among controls (n ¼ 136), cases of preeclampsia (n ¼ 169), and gestational hypertension (n ¼ 101) in the Calcium for Preeclampsia Prevention Trial, the results showed that copeptin levels at the baseline (<22 GW), second (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and third (33-38GW) measures positively associated with risk of PE, but were not associated with risk of GH. Marek et al [18] reported that the concentrations of copeptin in the second and third trimesters were significantly different between pregnancy-induced hypertension and the controls, but not in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…NAPRT1 is a cellular metabolic enzyme expressed in the placental trophoblast, which is known to prevent oxidative stress in several diseases including cancer [ 29 ]. This is important because the PE placenta is known to have high oxidative stress during this disease [ 48 , 49 ]. The fact that the NAPRT1 protein was decreased could drive the idea that this protein may be involved in the increased oxidative stress leading to the increased reactive oxidative species observed in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the motifs annotated by the source data, further annotation files were inferred based on motif similarity and gene sequences. The first step in estimating the overexpression of each motif across a gene set is to calculate the area under the curve (AUC) for each motif-motif-set pair ( 31 ). This calculation was performed based on the recovery curve calculation of the gene set versus motif ordering.…”
Section: Methodsmentioning
confidence: 99%